Upaya Meningkatkan Hasil Belajar Matematika Menggunakan Model Pembelajaran Contextual Teaching Learning Pada Siswa Kelas III SD Negeri III Buluk - Angelina Dea Miranda (MURABBI, 2023)
The research entitled "Efforts to Improve Mathematics Learning Outcomes Using the Contextual Teaching Learning Model for Grade III Students of Bluluk III Public Elementary School" aims to improve mathematics learning outcomes in fractional material through the contextual teaching learning model for third grade students of Bluluk III Public Elementary School. This research was compiled using classroom action research methods. Data collection through documentation, observation and interviews, and tests. With the actions taken by researchers using the CTL model, in cycle 1 the average value was 57.9. Then the researchers made improvements in cycle 2, and obtained an average score of 82. It can be concluded that the researchers were able to improve student learning outcomes in mathematics subject material for class III students at SD Negeri III Bluluk.